Genomic characterisation of Iraqi indigenous taurine x zebu crossbred cattle - Alshawi, Akil (2019)
Iraqi cattle breeds are found at the crossroad of the two main cattle regions of domestication; the Near East and the Northern part of the Indian subcontinent. There are currently four native breeds: Rustaqi (Central Iraq), Jenoubi (Southern Iraq), Sharabi (Northern Iraq - the Tigris Valley, north of Mosul), and Karradi (Northern Iraq in the Kurdistan region). In the harsh environments of Iraq (e.g. high tick prevalence and high temperatures), these native breeds have evolved to overcome these tough conditions. The genomic aspects of these adaptations here not yet been characterised.